Genome-Wide Off-Target Analysis in CRISPR-Cas9 Modified Mice and Their Offspring. Issue 11 (1st November 2019) - Dong, Yan; Li, Haimei; Zhao, Liang; Koopman, Peter; Zhang, Feng; Huang, Johnny X
Abstract: The emergence of the CRISPR-Cas9 system has triggered a technical revolution in mammalian genome editing. Compared to traditional gene-targeting strategies, CRISPR-Cas9 technology offers a more efficient and cost-effective approach for generating genetically modified animal models. However, off-target cleavage in CRISPR-mediated genome editing is a major concern in the analysis of phenotypes as well as the selection of therapeutic targets. Here, we analyzed whole-genome sequencing (WGS) data from two knock-out (KO) mouse strains generated by using the CRISPR-Cas9 system targeting the Mmd and Paqr8 loci. A total of nine individuals were sequenced including two parents, four F1 offspring and three uninjected control mice. Using GATK and bcftools software, we identified two off-target events in the founder mice. The two CRISPR-Cas9-induced off-target events were predictable using Cas-OFFinder and were not passed on to the offspring that we investigated. In addition, our results indicated that the number of CRISPR-Cas9-induced mutations was not statistically distinguishable from the background de novo mutations (DNMs).